KEPRIBADIAN DAN LINGKUNGAN KERJA: STUDI PSYCHOLOGICAL WELL-BEING PADA ANGGOTA SATUAN KAPAL SELAM TNI AL - Yudha Diky Pradipta; Rini Nurahaju; Gartinia Nurcholis (Fakultas Psikologi Universitas Hang Tuah, 2021)
Members of the submarine unit have limited and small environmental conditions that can affect the lives of members of the submarine unit. The life of a member of a submarine can pay attention to physical well-being and psychological well-being. The current study examined the impact of personality and work environment with psychological well-being among members of submarine unit Angkatan Laut Indonesia. A total of 86 members of submarine unit Angkatan Laut Indonesia were recruited through accidental sampling. The Measuring instruments were personality scales, work environment scale, and psychological well-being scale. Data were analyzed using multiple linear regression analysis techniques. The results showed that there was a simultaneous effect between personality and work environment on psychological well-being with a simultaneous contribution of 55.2%.